'Orderly made': re-appraising household inventories in seventeenth-century England. (1st October 2016) - Spaeth, Donald
Abstract: The amateur appraisers who prepared probate inventories were commentators on social and economic change in early modern England. This article considers the form these sources took, to illuminate the thinking of appraisers and the social context of appraising. Although historians recognise the limitations of inventories, they have paid little attention to them as records of the act of appraisal. Through a case study of one seventeenth-century town – Thame in Oxfordshire – individual styles of appraising are explored. Inventories were representations, based on conscious reflection about how to arrange these ordered lists. Appraising had its own history, and approaches changed over time in response to the growing number of household goods and spaces. Broad participation supported a culture of appraisal, but a small number of mostly better-off individuals were often able to control the process, using specialist skills. The study of appraisal brings to life the cooper Andrew Parslow, the town's dominant appraiser in the late seventeenth century, who devised an entirely new 'summary' format, and whose standing in society depended upon his role as an appraiser. Parslow's practice is significant in demonstrating how appraisers devised new ways of representing material culture during the century, as their understandings of possessions changed.